PERBEDAAN EFEKTIVITAS DOSIS CAMPURAN KAPUR TOHOR DAN KAPUR BARUS TERHADAP PENURUNAN KEPADATAN LALAT PADA SAMPAH ORGANIK DI TEMPAT PENAMPUNGAN SEMENTARA (TPS) PASAR CIKURUBUK KOTA TASIKMALAYA - Putra, Adithya Pratama; Setiyono, Andik; Maywati, Sri (Jurnal Kesehatan Komunitas Indonesia, 2023)
All economic activities that take place in the market will always produce waste. The Cikurubuk Market Temporary Dumpster (TPS) in Tasikmalaya City has not been managed properly so that it became a breeding place for flies. The application of quicklime and camphor is one of the fly control measures that can be taken in their breeding places. The goal og research to determined the difference in the effectiveness of doses of camphor and camphor mixture on reducing fly density in TPS and to found the most effective dose. The methode is experimental research and post-test only control group design. The independent variable in this study was the dose of camphor and camphor mixture, while the dependent variable was fly density. The population in this study were all flies in the Cikurubuk Market TPS in Tasikmalaya City. The samples in this study were flies trapped by fly traps. Data analysis in this study used one way anova statistical test with post hoc least significant differences (LSD) test. The results showed that the highest mean of fly density was obtained in the control group which was 16.33 flies. The lowest mean of fly density was obtained in the dose 6 treatment group, which was 5.67 flies. The results of statistical tests showed that there were differences in fly density based on variations in the dose of a mixture of quicklime and camphor in organic waste (p value = 0.000). The results of the post hoc test showed that dose 6 (5 grams of quicklime and 5 grams of camphor) was the most effective treatment group in reducing fly density in organic waste with a mean difference value of 10.667. The suggestion is necessary to take fly control measures by applying a mixture of lime and camphor to organic waste at a dose of 5 grams of lime and 5 grams of camphor per 10 liters of organic waste.